以《了凡四訓·立命篇》論袁了凡的命觀及其思想 = A study on Liao-Fan's fate concept - Liu, Haihuang (2016)
《了凡四訓》成書於明朝，其作者是袁黃（1535-1606），字坤儀，號學海後改為了凡，浙江嘉善人。袁了凡通過自身成功改變運命的人生際遇，寫下該書以訓誡自己的後代子孫，告誡後人命運是可改變的，並提供一套完善的理論方法。《了凡四訓》是在三教合一思潮興盛的明朝背景下成書的，它體現出「儒釋道」三家合一的色彩。它是以儒家的道德思想為核心，兼涉取佛教的出世觀、因果觀；道家的承負說、養生觀等，可謂是「三教融通」。《了凡四訓》是由「立命之學」、「改過之法」、「積善之方」和「謙德之效」四篇文章組成的。而<立命篇>具有開宗明義之效，可說是全書之精華所在，故本文將以它為主要研究對象。它闡述「命由我作，福自己求」的立命觀。它強調人的命運是可通過後天的斷惡修善，積功累德而往好的方向發展，如轉禍為福；並深信「積善之家，必有餘慶；積不善之家，必有餘殃」的因果思想。「立命」二字早在戰國時期雖已被儒家大賢孟子提出，然袁黃卻賦予了新的詮釋，即人具有掌握命運的主動權和積極性。被日本著名漢學家安岡正篤譽為「人生能動的偉大學問」的《了凡四訓》對於現今社會不只有借鑒意義，它還為個人提供安身立命之道和積極向上的人生態度。<立命篇>不僅破除宿命論，它給予絕望中的人們希望與寄託，這對生活在物慾橫流的現今社會的人們有着安定人心的作用。Yuan Huang(1535-1606) was the author of Liao Fan Si Xun which was published during the Ming dynasty. This book relates how Yuan Huang changed his destiny through actions such as doing good deeds and becoming a better person. Yuan Huang hoped that this book with its theoretical methods could help his descendants change their lives. Liao Fan Si Xun was the result of the integration between the three main thoughts during the Ming dynasty. It consists of Confucianism, Taoism and Buddhism. These three thoughts were well integrated by Yuan Huang in this book. Liao Fan Si Xun consists of four different chapters and Li Ming Pian, being the first chapter was the utmost important of all, and it was about how to change one’s destiny, hence this thesis would focus mainly on it. Although the concept of fate have been discussed since the pre-Qin dynasty, it mainly discussed the idea of the existence of fate and human beings are merely followers and have no control over it. However, Yuan Huang’s view of fate was totally different. He brought up the idea that one could change their own destiny via accumulating good deeds and even provide a set of guidelines and theories. Liao Fan Si Xun has been highly valued by people from different parts of the world. For instance, the Japanese leaders used it as reference to lead their country. This thesis hoped to explore Yuan Huang’s fate concept as well as his thought. Lastly, this thesis would discuss how Liao Fan Si Xun would benefit us.